Accurate evaluation of aberration for probe-forming system and influence of aberration on high-resolution STEM image - Sawada, H; Hosokawa, F; Kirkland, A (Insitute of Physics, 2017)
The influence of residual three-fold astigmatism on high-resolution STEM imaging of graphene has been investigated. The aberration was measured by the segmented Ronchigram auto-correlation function method using the graphene lattice. In the presence of residual threefold astigmatism the graphene lattice showed a lower three-fold rotational symmetry where three C atoms in the six membered ring had a higher intensity.